Prognostic Significance of Myocardial Blood Flow Quantification for Major Adverse Cardiac Events: A Systematic Review and Meta-analysis. Issue 3 (2nd March 2022) - Pan, Changjie; Yin, Ruohan; Tang, Xiaoqiang; Wang, Tao; Hu, Chunhong
Abstract : Chronic coronary syndromes involve reduced myocardial blood flow (MBF). MBF is a reliable predictor of outcomes, independent of the presence of significant stenosis. Whether MBF can predict major adverse cardiac events (MACE) during long-term follow-up is unknown. PubMed, Embase, Cochrane, CNKI, and WANFANG were searched for papers published up to January 2021. The exposure was the incremental unit of stress MBF (mL/g/min) or low MBF versus high MBF. The imaging examinations included positron emission tomography/computed tomography and coronary magnetic resonance. The study outcome was the occurrence of MACE during follow-up, summarized as time-to-event hazard ratios (HRs) and 95% confidence intervals (CIs). Six studies (300 MACEs in 2326 patients) were included. Four studies presented stress MBF data by unit increments. The pooled HR showed that an increase in stress MBF by 1 mL/g/min is a protective factor for MACE (HR = 0.32; 95% CI, 0.18–0.57; I 2 = 62.9%, Pheterogeneity = 0.044). Two studies reported stress MBF as low/high. The results showed that a high-stress MBF was protective against MACEs (HR = 0.43; 95% CI, 0.24–0.78; I 2 = 39.5%, Pheterogeneity = 0.199). Quantification of stress MBF using positron emission tomography/computed tomography and coronary magnetic resonance might have incremental predictive value for future MACEs in a population at intermediate to high cardiovascular risk. The results will require validation in large prospective randomized controlled trials.